2012
DOI: 10.3389/fnhum.2012.00059
|View full text |Cite
|
Sign up to set email alerts
|

Do we care about the powerless third? An ERP study of the three-person ultimatum game

Abstract: Recent years have provided increasing insights into the factors affecting economic decision-making. Little is known about how these factors influence decisions that also bear consequences for other people. We examined whether decisions that also affected a third, passive player modulate the behavioral and neural responses to monetary offers in a modified version of the three-person ultimatum game. We aimed to elucidate to what extent social preferences affect early neuronal processing when subjects were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 45 publications
6
59
0
1
Order By: Relevance
“…Our observation of fairness-dependent FRN deflections in the third party perspective appears to be in accordance with findings by Hewig et al (2008) who reported larger FRN amplitudes also when others are observed experiencing disadvantageous outcomes (however, see also for diverging results: Alexopoulos, Pfabigan, Lamm, Bauer, & Fischmeister, 2012;Alexopoulos, Pfabigan, Göschl, Bauer, & Fischmeister, 2013). One could speculate that such FRN modulations occur due to the observed violation of fairness norms.…”
Section: Frnsupporting
confidence: 81%
“…Our observation of fairness-dependent FRN deflections in the third party perspective appears to be in accordance with findings by Hewig et al (2008) who reported larger FRN amplitudes also when others are observed experiencing disadvantageous outcomes (however, see also for diverging results: Alexopoulos, Pfabigan, Lamm, Bauer, & Fischmeister, 2012;Alexopoulos, Pfabigan, Göschl, Bauer, & Fischmeister, 2013). One could speculate that such FRN modulations occur due to the observed violation of fairness norms.…”
Section: Frnsupporting
confidence: 81%
“…As to the electrophysiological response, we expect to observe a greater negativity of the FRN in response to unfair and mid-value offers than to fair offers, as in previous studies (Polezzi et al, 2008;Wu et al, 2011Wu et al, , 2012Alexopoulos et al, 2012Alexopoulos et al, , 2013Qu et al, 2013). Since the FRN is thought to be sensitive to socio-emotional evaluation of the game partners (Campanhã et al, 2011;Qu et al, 2013) and to social expectancy violation (Boksem and DeCremer, 2010;Wu et al, 2012), we may observe greater FRN effects whenever social expectations are not met (Wu et al, 2011(Wu et al, , 2012Qu et al, 2013;Alexopoulos et al, 2013).…”
Section: The Present Studymentioning
confidence: 74%
“…A recent study showed that the nature of the shares offered to the third person in the third ultimatum game paradigm did not affect the amplitude of the FRN of the participants playing as responders (Alexopoulos et al, 2012(Alexopoulos et al, , 2013. Moreover, another study also demonstrated that making the responders compare the share they were proposed to shares received by others responders playing in different players' dyad did not lead to a modulation of the amplitude of the FRN (Wu et al, 2011).…”
Section: Electrophysiological Correlates Of the Responder Playing Thementioning
confidence: 90%
See 2 more Smart Citations